A cold-induced high-strength conductive eutectic hydrogel and its preparation method and application
By introducing a mixed solvent of DES and water, choline chloride and carboxylic acid in Kede Gel, a low eutectic hydrogel is formed, which solves the problems of poor mechanical properties and non-conductivity of Kede Gel, and achieves high strength , the improvement of conductivity and weather resistance, suitable for a variety of biomedical and electronic applications.
Patent Information
- Application Number
- CN202211537706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-12-02
AI Technical Summary
In biomedical applications, Kede Glue Gel has poor mechanical properties, poor weather resistance and no conductivity, making it difficult to meet the requirements of the biomedical field.
DES and water are used to form a mixed solvent as the gel dispersion medium, and through heating and cooling processes, Kede Gum forms a high-strength low eutectic hydrogel, and choline chloride and carboxylic acid are introduced as hydrogen bond acceptors and donors. Promote the cross-linking and ionization of Kede Gum molecules to form a gel with excellent mechanical properties and electrical conductivity.
The prepared Kede Gum Low Eutectic Hydrogel has excellent mechanical properties, conductivity, stretchability, compressibility, flexibility and antibacterial properties, and is suitable for 3D printing, tissue engineering, drug carriers, medical dressings, flexible electronics, etc. field.
Smart Images

Figure BDA0003978423280000081 
Figure BDA0003978423280000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials and relates to a method for preparing a cold-induced high-strength conductive eutectic hydrogel. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Curdlan is the only straight-chain pure glucan composed entirely of β-1,3-D-glucose units, also known as curdlan, gellan or thermogellan. Curdlan's unique pharmacological properties have attracted much attention in the biomedical field, but even at higher temperatures, the mechanical properties of the hydrogel formed by physical self-crosslinking of curdlan macromolecules still cannot meet most application requirements in the biomedical field. For example, as a tissue engineering material, curdlan hydrogel lacks certain toughness and tissue load capacity, especially high-temperature gelation, which limits the biomedical application of curdlan to a certain extent. Curdlan hydrogel not only has poor mechanical properties, but also has poor weather resistance due to the volatility and high freezing point of water as the dispersion medium. Although there are literature reports that curdlan gel with organic solvents such as glycerol and DMSO as the dispersion medium can improve mechanical properties and weather resistance to a certain extent, this type of curdlan gel is not conductive. Therefore, how to solve the problems of poor mechanical properties, poor weather resistance and non-conductivity of the prepared curdlan hydrogel has become an urgent need. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing and applying a cold-induced high-strength conductive eutectic hydrogel of desiccant glue. In the preparation process, DES is introduced into the method, and a mixed solvent formed by DES and water is used as a gel dispersion medium. The prepared eutectic hydrogel of desiccant glue has excellent mechanical properties and conductivity, and is stretchable, compressible, flexible and elastic.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] On the one hand, a method for preparing a cold-induced high-strength eutectic hydrogel of curd, comprising:
[0007] 1) mixing a hydrogen bond acceptor and a hydrogen bond donor, heating and stirring until a clear and transparent solution is obtained, and cooling to obtain a deep eutectic solvent DES;
[0008] 2) mixing the DES obtained in step 1) with water to obtain a DES-water mixed solvent;
[0009] 3) adding the caldnoic acid to the DES-water mixed solvent obtained in step 2) and stirring to obtain a dispersion;
[0010] 4) transferring the dispersion obtained in step 3) to a mold, heating it in a constant temperature water bath, taking it out and cooling it to obtain;
[0011] The hydrogen bond acceptor is one or both of choline chloride and betaine; and the hydrogen bond donor is carboxylic acid.
[0012] On the other hand, a cold-induced high-strength calendulite low-eutectic hydrogel is obtained by the above preparation method.
[0013] In a third aspect, the present invention also provides applications of cold-induced high-strength eutectic hydrogels in 3D printing, tissue engineering, drug carriers, medical dressings, and flexible electronics.
[0014] One or more technical solutions of the present invention have the following beneficial effects:
[0015] 1. The preparation method and process of the eutectic hydrogel of the present invention are simple. The pretreated dispersion forms a uniform solution when heated and forms a gel (cryogel) when cooled. The raw materials involved in the preparation process are naturally renewable, biocompatible and biodegradable, environmentally friendly and pollution-free.
[0016] 2. The present invention introduces DES in the preparation process, and forms a mixed solvent with water as a gel dispersion medium, which improves the mechanical properties and weather resistance of the calendulum gel, and increases the conductivity of the gel. The performance of the gel can be regulated by changing the composition of the low eutectic solvent, the ratio of the low eutectic solvent to water, the concentration of the calendulum, the heating temperature and time. The calendulum low eutectic hydrogel prepared by the method of the present invention has excellent mechanical properties and conductivity, is stretchable, compressible, flexible and elastic, and has antibacterial properties, and has broad application prospects in 3D printing, tissue engineering, drug carriers, medical dressings, flexible electronics, etc. DETAILED DESCRIPTION
[0017] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0018] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0019] In view of the fact that the existing caldner hydrogel has poor mechanical properties, poor weather resistance and is non-conductive, the present invention proposes a method for preparing a cold-induced high-strength caldner low-eutectic hydrogel.
[0020] A typical embodiment of the present invention is a method for preparing a cold-induced high-strength eutectic hydrogel of curd, comprising:
[0021] 1) mixing a hydrogen bond acceptor and a hydrogen bond donor, heating and stirring until a clear and transparent solution is obtained, and cooling to obtain a deep eutectic solvent DES;
[0022] 2) mixing the DES obtained in step 1) with water to obtain a DES-water mixed solvent;
[0023] 3) adding the caldnoic acid to the DES-water mixed solvent obtained in step 2) and stirring to obtain a dispersion;
[0024] 4) transferring the dispersion obtained in step 3) to a mold, heating it in a constant temperature water bath, taking it out and cooling it to obtain;
[0025] The hydrogen bond acceptor is one or both of choline chloride and betaine; and the hydrogen bond donor is carboxylic acid.
[0026] As a new type of solvent, deep eutectic solvents (DES), especially natural deep eutectic solvents (NADES), have attracted much attention in recent years. DES is prepared by combining hydrogen bond acceptors (such as quaternary ammonium salts such as choline chloride and betaine) with hydrogen bond donors (such as urea, carboxylic acids, polyols, etc.). When natural components are used to prepare DES, NADES is obtained. DES is similar to ionic liquids, with low volatility and most of them have good conductivity; but compared with ionic liquids, DES has the advantages of simple preparation method, no separation and purification steps, low cost, good biocompatibility, and most of them are non-toxic or low toxic. Therefore, using DES as a dispersion medium for gels to partially or completely replace traditional water media has attracted much attention in recent years, and the product has immeasurable prospects in biomedicine, energy, electronics and environmental science.
[0027] The present invention introduces DES in the preparation process, and forms a mixed solvent with water as a gel dispersion medium. On the one hand, when the temperature rises, DES promotes the destruction of hydrogen bonds in the caldnolide molecules to form a uniform solution; on the other hand, when the temperature drops, DES promotes the caldnolide molecules to self-assemble into a helical structure, and the helical structures are cross-linked to form a high-strength gel. In addition, choline chloride and carboxylic acid are ionized in water to make the gel have ionic conductivity, especially choline chloride is easy to ionize.
[0028] In some examples of this embodiment, the carboxylic acid is one or more of lactic acid, malic acid, citric acid, tartaric acid, and oxalic acid.
[0029] In some examples of this embodiment, when the carboxylic acid is lactic acid, the molar ratio of choline chloride to lactic acid is 1:6-10, preferably 1:8.
[0030] In some examples of this embodiment, when the carboxylic acid is malic acid, the molar ratio of choline chloride to malic acid is 1:2 to 3, preferably 1:2.
[0031] In some examples of this embodiment, when the carboxylic acid is citric acid, the molar ratio of choline chloride to citric acid is 1:1 to 3, preferably 1:1.
[0032] In some examples of this embodiment, in step 1), the temperature during stirring is 60-90° C.; and the cooling temperature is room temperature.
[0033] In some examples of this embodiment, the mass ratio of DES to water is 1:1-9, preferably 1:1.5.
[0034] In some examples of this embodiment, in step 3), during stirring, the temperature is 15 to 25° C., preferably 15 to 18° C.; and the stirring time is 1 to 3 h, preferably 2 h.
[0035] In some examples of this embodiment, the mass concentration of the curd gum in the dispersion is 2% to 5%.
[0036] In some examples of this embodiment, in step 4), the heating temperature is 60 to 90° C., preferably 60 to 80° C.; the heating time is 2 to 10 min, preferably 2 to 5 min.
[0037] In some examples of this embodiment, in step 4), the cooling temperature is 10-20° C., preferably 15-18° C.; the cooling time is 12-24 h, preferably 18 h.
[0038] Another embodiment of the present invention provides a cold-induced high-strength calendulum low-eutectic hydrogel obtained by the above-mentioned preparation method.
[0039] A third embodiment of the present invention provides applications of cold-induced high-strength eutectic hydrogels in 3D printing, tissue engineering, drug carriers, medical dressings, and flexible electronics.
[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0041] Example 1
[0042] 1.58g of choline chloride was mixed with 10.18g of lactic acid, heated and stirred at 80°C for 30min, and cooled to room temperature; 11.76g of deionized water was added, and 0.48g of caldwelling gum was added under stirring, and stirring was continued at room temperature for 2h; the mixture was transferred into a mold, and then the mold containing the uniform dispersion of caldwelling gum was placed in a 60°C constant temperature water bath, taken out after 5min, and cooled to room temperature to obtain a caldwelling gum low eutectic hydrogel. The compressive strength of the low eutectic hydrogel was 0.364±0.012MPa, and the compression fracture deformation was 87.04±0.94%; the tensile strength of the low eutectic hydrogel was 14.87±0.19kPa, and the tensile fracture elongation was 161.45±22.73%. The conductivity of the low eutectic hydrogel was 1.769±0.067S / m.
[0043] Example 2
[0044] Example 1 was repeated, except that the mold containing the uniform dispersion of caldane was placed in a 70°C constant temperature water bath and taken out after 5 minutes; the compressive strength of the low eutectic hydrogel was 0.298±0.008MPa, the compression fracture deformation was 91.68±1.01%, the tensile strength was 12.80±1.9kPa, and the tensile fracture elongation was 155.21±21.06%. The electrical conductivity of the low eutectic hydrogel was 1.863±0.053S / m.
[0045] Example 3
[0046] Example 1 was repeated, except that the mold containing the uniform dispersion of curdlan was placed in a constant temperature water bath at 80°C and taken out after 4 minutes; the compressive strength of the low eutectic hydrogel was 0.294±0.017MPa, the compression fracture deformation was 85.23±0.56%, the tensile strength was 12.25±0.20kPa, and the tensile fracture elongation was 142.41±1.75%. The electrical conductivity of the low eutectic hydrogel was 1.759±0.099S / m.
[0047] Example 4
[0048] Example 1 was repeated, except that the mold containing the uniform dispersion of curdlan was placed in a 90°C constant temperature water bath and taken out after 2 minutes; the compressive stress of the low eutectic hydrogel was 0.222±0.027MPa, the compression fracture deformation was 86.44±2.51%, the tensile strength was 5.85±0.64kPa, and the tensile fracture elongation was 86.51±0.12%. The electrical conductivity of the low eutectic hydrogel was 1.753±0.048S / m.
[0049] Example 5
[0050] Example 1 was repeated, except that: 1.53 g of choline chloride was mixed with 9.87 g of lactic acid, heated and stirred at 80°C for 30 min, and cooled to room temperature; 11.40 g of deionized water was added, and 1.20 g of calcite was added while stirring, and stirring was continued at room temperature for 2 h. The compressive stress of the low eutectic hydrogel at 90% deformation was 0.801 ± 0.083 MPa; the tensile strength of the low eutectic hydrogel was 69.65 ± 3.20 kPa, and the tensile elongation at break was 277.74 ± 3.76%. The electrical conductivity of the low eutectic hydrogel was 1.506 ± 0.004 S / m.
[0051] Example 6
[0052] Example 5 was repeated, except that 0.31 g of choline chloride was mixed with 1.97 g of lactic acid, heated and stirred at 80°C for 30 min, and 20.52 g of deionized water was added after cooling to room temperature. The compressive strength of the low eutectic hydrogel was 0.325±0.019 MPa, and the fracture deformation was 87.47±3.17%; the tensile strength of the low eutectic hydrogel was 13.73±1.27 kPa, and the tensile elongation at break was 99.85±15.37%. The electrical conductivity of the low eutectic hydrogel was 1.121±0.003 S / m.
[0053] Example 7
[0054] Example 5 was repeated, except that 1.22 g of choline chloride was mixed with 7.90 g of lactic acid, heated and stirred at 80°C for 30 min, and 13.68 g of deionized water was added after cooling to room temperature. The compressive stress of the low eutectic hydrogel at 90% deformation was 1.493±0.061 MPa; the tensile strength of the low eutectic hydrogel was 123.10±3.20 kPa, and the tensile elongation at break was 295.23±9.30%. The electrical conductivity of the low eutectic hydrogel was 1.663±0.117 S / m.
[0055] Example 8
[0056] Example 5 was repeated, except that 1.48 g of choline chloride was mixed with 7.64 g of lactic acid, heated and stirred at 80°C for 30 min, and 13.68 g of deionized water was added after cooling to room temperature. The compressive stress of the low eutectic hydrogel at 90% deformation was 2.002±0.032 MPa; the tensile strength of the low eutectic hydrogel was 103.40±10.75 kPa, and the tensile elongation at break was 203.50±2.68%. The electrical conductivity of the low eutectic hydrogel was 1.820±0.047 S / m.
[0057] Example 9
[0058] Example 5 was repeated, except that: 1.87 g of choline chloride was mixed with 7.25 g of lactic acid, heated and stirred at 80°C for 30 min, and cooled to room temperature; 13.68 g of deionized water was added, and 1.20 g of calcite was added while stirring, and stirring was continued at room temperature for 2 h. The compressive stress of the low eutectic hydrogel at 90% deformation was 1.769 ± 0.004 MPa; the tensile strength of the low eutectic hydrogel was 74.00 ± 1.56 kPa, and the tensile elongation at break was 168.00 ± 1.23%. The electrical conductivity of the low eutectic hydrogel was 2.223 ± 0.040 S / m.
[0059] Example 10
[0060] Example 1 was repeated, except that 4.03 g of choline chloride was mixed with 7.73 g of malic acid. The compressive stress of the low eutectic hydrogel at 90% compressive strain was 0.403 ± 0.016 MPa; the tensile strength of the low eutectic hydrogel was 16.67 ± 0.22 kPa, and the tensile elongation at break was 143.39 ± 12.03%. The electrical conductivity of the low eutectic hydrogel was 2.987 ± 0.177 S / m.
[0061] Embodiment 11
[0062] Example 1 was repeated, except that 4.95 g of choline chloride was mixed with 6.81 g of citric acid. The compressive stress of the low eutectic hydrogel at 90% deformation was 0.458 ± 0.095 MPa; the tensile strength of the low eutectic hydrogel was 21.30 ± 3.25 kPa, and the tensile elongation at break was 117.11 ± 10.46%. The electrical conductivity of the low eutectic hydrogel was 3.493 ± 0.166 S / m.
[0063] Comparative Example
[0064] 1.20g of caldane was added to 22.80g of deionized water, stirred at room temperature for 2h, and then the caldane dispersion was transferred into a mold. The mold containing the caldane dispersion was placed in a 60℃ constant temperature water bath, taken out after 5min, and cooled to room temperature to obtain caldane hydrogel. The compressive strength of the caldane hydrogel was 0.155±0.006MPa, and the compression fracture deformation was 82.53±0.31%; the tensile strength was 6.90±0.70kPa, and the tensile fracture elongation was 69.26±9.29%. The conductivity of the caldane hydrogel was 0.134±0.007S / m.
[0065] The mechanical properties and conductive properties of the low eutectic hydrogels obtained in the above examples are listed in Table 1, respectively.
[0066] Table 1 Mechanical properties and conductive properties of cold-induced high-strength conductive eutectic hydrogel
[0067]
[0068]
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cold-induced high-strength conductive eutectic hydrogel, characterized in that: include: 1) Mix the hydrogen bond acceptor and the hydrogen bond donor, heat and stir until a clear and transparent solution is obtained, and cool to obtain a low eutectic solvent DES; 2) mixing the DES obtained in step 1) with water to obtain a DES-water mixed solvent; 3) adding the caldnoic acid to the DES-water mixed solvent obtained in step 2) and stirring to obtain a dispersion; 4) The dispersion obtained in step 3) is transferred to a mold, heated in a constant temperature water bath, taken out and cooled, and the mold is obtained; The hydrogen bond acceptor is choline chloride; the hydrogen bond donor is a carboxylic acid; the carboxylic acid is one of lactic acid, malic acid and citric acid; when the carboxylic acid is lactic acid, the molar ratio of choline chloride to lactic acid is 1:6-10; when the carboxylic acid is malic acid, the molar ratio of choline chloride to malic acid is 1:2-3; when the carboxylic acid is citric acid, the molar ratio of choline chloride to citric acid is 1:1-3; The mass ratio of DES to water is 1:1.
5.
2. The preparation method according to claim 1, characterized in that: The carboxylic acid is lactic acid, and the molar ratio of choline chloride to lactic acid is 1:
8.
3. The preparation method according to claim 1, characterized in that: The carboxylic acid is malic acid, and the molar ratio of choline chloride to malic acid is 1:
2.
4. The preparation method according to claim 1, characterized in that: The carboxylic acid is citric acid, and the molar ratio of choline chloride to citric acid is 1:
1.
5. The preparation method according to claim 1, characterized in that: In step 1), the temperature during stirring is 60-90°C; the cooling temperature is room temperature.
6. The preparation method according to claim 1, characterized in that: In step 3), the stirring temperature is 15-25°C and the stirring time is 1-3 h.
7. The preparation method according to claim 6, characterized in that: In step 3), the temperature during stirring is 15-18°C and the stirring time is 2h.
8. The preparation method according to claim 1, characterized in that: In step 4), the heating temperature is 60-90° C. and the heating time is 2-10 min.
9. The preparation method according to claim 8, characterized in that: In step 4), the heating temperature is 60-80°C and the heating time is 2-5 min.
10. The preparation method according to claim 1, characterized in that: In step 4), the cooling temperature is 10-20°C and the cooling time is 12-24h.
11. The preparation method according to claim 10, characterized in that: In step 4), the cooling temperature is 15-18°C and the cooling time is 18 h.
12. The cold-induced high-strength conductive eutectic hydrogel prepared by any one of the preparation methods of claims 1 to 11.
13. Application of the cold-induced high-strength conductive eutectic hydrogel according to claim 12 in 3D printing and flexible electronics; Or, the use of the cold-induced high-strength conductive eutectic hydrogel according to claim 12 in the preparation of tissue engineering products, the preparation of drug carriers or the preparation of medical dressing products.
